A review of the prevalence of Acinetobacter that contains the blaNDM-1 Gene - Rabbi, Ashikan; Tooli, Atoshi Debnath (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2022.